Réponses

2013-05-15T15:23:12+02:00
B. Soit x+2=0
x=-2
Soit 3x+5=0
3x=-5
X=-5/3
Soit 7x-3=0
7x=3
X=3/7
2013-05-15T15:25:57+02:00

a)  3x(x-2) =0

= 3x²-6x=0

 

b) (x+2)(3x+5) (7x-3)=0

= 3x+5x+6x+10=0

= 14x+10=0

 

c)  5 (x²+1) (3x-4) =0

= 5x²+5+15x-20 = 0

= 5x²+15x-15=0

 

d)(t-1) (2t+5) (4t-3) =0

=2t²+5t-2t+5 + 4t²-3t - 4t-3=0

=6t² -4t +2=0

 

e). (x+2) (3x-5) =0

=3x²-5x + 6x-10=0

=3x² +1x -10 = 0

 

f) x+2 (3x-5) =0

x + 6x-10=0

7x-10=0

 

g) x²-4 =0

 

h). x (x-3) +2 (x-3) =0

= x²-3x + 2x-6=0

x²-1x-6=0